Pengelolaan Dana Zakat, Infak, Dan Sedekah (Studi Kasus di Baituzzakah Pertamina Balikpapan) - Utomo, Danang Prakoso; , Mutimatun Ni'ami, S.H., M.H um; , Darsono, S.H., M.H (2015)
Zakat is a very important subsystem in supporting the economy of a nation. In Islam, zakat is essential element and must be carried out as it is written in the fourth pillar of Islam. Zakat management in Baituzzakah Pertamina Balikpapan City becomes one of essential elements which accommodates Muslim employees of Pertamina Balikpapan who wants to pay zakat, and also helping the government of Balikpapan for the welfare of its citizens, especially the poor and those who deserve it. Based on Act No. 23 of 2011 on The Management of Zakat and other regulations, which contents are the rights of the poor and the obligation for Muslims who have fixed income to pay zakat.